Membangun Kapasitas Tata Kelola Pengawasan Ketenagakerjaan Bidang Keselamatan dan Kesehatan Kerja (K3): The Building Governance Capacity for Labor Inspection in Occupational Safety and Health (OSH) - Rozikin, Mochammad (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
The issue of implementing national K3 labor inspection includes two main aspects, namely governance and capacity building. The two main issues relate to weak awareness of the importance of implementing OSHMS in the workplace, weak understanding of K3 as part of human rights, weak criminal sanctions related to K3, relatively low coverage of K3 supervision, overlapping technical K3 regulations between institutions, weak quality, quantity and competence of K3, as well as the lack of synergy and integration of the operational supervision system between the central and regional governments. The author analyzes empirical data and reviews previous research using a systematic flow prism framework, and juxtaposes it with the fundamental theoretical concepts of governance, capacity building and labor inspection. The results of the analysis produce a hypothetical framework for building capacity for labor inspection governance in the K3 sector. This requires strategic intervention in human resource capacity, organizations and institutions, as well as governance that needs to be jointly constructed on the basis of an agreement on the principle of joint involvement. So, during the management and implementation process, each stakeholder/actor can be adaptive, the system and implementation of supervision can be more effective and efficient, where continuity and feedback from the accumulated process can reduce the impact and influence of uncertainty and the dynamics of a dynamic workforce environment.